Self-reported occupational physical activity and cardiorespiratory fitness: Importance for cardiovascular disease and all-cause mortality - Andreas Holtermann; Jacob L Marott; Finn Gyntelberg; Karen Søgaard; Ole Steen Mortensen; Eva Prescott; Peter Schnohr (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: This study aimed to investigate whether workers with the combination of high occupational physical activity (OPA) and low cardiorespiratory fitness have an increased risk of cardiovascular disease (CVD) and all-cause mortality. METHODS: Using multivariable Cox proportional hazards regression, we analyzed 2190 males and 2534 females from the Copenhagen City Heart Study, aged 20-67 years and with no known CVD at study entry in 1991-1994, for the risk of CVD and all-cause mortality from independent, stratified and combinations of self-reported OPA (ie, low, moderate and high) and cardiorespiratory fitness (low, same and higher as peers) at baseline. RESULTS: During a median follow-up of 18.5 years, 257 and 852 individuals died from CVD and any cause, respectively. In the fully-adjusted model, an increased risk for CVD mortality was found for those with low compared to high self-reported cardiorespiratory fitness [hazard ratio (HR) 2.17, 95% confidence interval (95% CI) 1.40-3.38), for those with high compared to low OPA (HR 1.45, 95% CI 1.05-2.00), and for those with high compared to low OPA within the strata of low self-reported cardiorespiratory fitness (HR 2.83, 95% CI 1.24-6.46). Moreover, those with the combination of high OPA and low self-reported cardiorespiratory fitness had an increased risk for CVD mortality compared to those with the combination of low OPA and high self-reported cardiorespiratory fitness (HR 6.22, 95% CI 2.67-14.49). Rather similar, but lower risk estimates were found for all-cause mortality. CONCLUSION: These findings may have important implications for CVD prevention among workers with excessive cardiovascular strain at work.